KEPRIBADIAN RASULULLAH SAW SEBAGAI GURU PROFESIONAL - Zulhammi, Zulhammi (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2014)
AbstractA professional teacher has a good educated and drill man in doing job and obligation as a teacher. He/she must fill him/herself all knowledge, character and competence in education such religius paedagogic, personality-religius, social-religious, and professional-religius. In Islam, to represent a profesional teahcer can adopt the system done by Muhammad (Peace be Upen Him) because he has a qualified character as a teacher.Keywords: Character, Muhammad, and a Professional Teacher